A new eremophilane-sesquiterpene from the cultured lichen mycobiont of Graphis sp. Issue 1 (22nd December 2021) - Vo, Van Giau; Le, Hoang-Duy; Tran, Thanh-Nha; Nguyen, Ngoc-Hong; Vo, Thi-Phi Giao; Sichaem, Jirapast; Nguyen, Van-Kieu; Duong, Thuc-Huy
Abstract: Lichens, a natural source producing a number of valuable compounds is economically not feasible and profitable due to its slow growth. Mycobiont cultures are alternative sources which have become highly attractive for chemists recently. Mycobiont of Graphis sp., a native lichens in Vietnam was separated then cultivated in test tubes. The present study aimed to identify chemical constituents of the cultured mycobiont of Graphis sp. Multiple chromatographic methods were applied to isolate three eremophilane sesquiterpenes including one new compound, graphilane (1 ) and two known compounds sporogen-AO-1 (2 ) and dihydrosporogen-AO-1 (3 ). Their chemical structures was elucidated by extensive 1 D and 2 D NMR analysis and high resolution mass spectroscopy as well as comparisons in literature. Compound 1 was evaluated for the cytotoxic activity against K562 cancer cell line and revealed moderate activity with IC50 value of 87.20 ± 0.76 µM. Abstract : UF0001